School Bullying In Southeast Asia Countries: Categories, Elements And Incidences - Ab Ghani, Sayuti; Mahzan Awang, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
UNICEF and The Association of Southeast Asian Nations (ASEAN) are highly emphasisig the importance of students well-being. All schools need to take serious actions to prevent from ny violences and bullying incidences. This paper clarifies the category of bullying behaviour based on past reports. It also analyses reports on bullying incidences in six ASEAN members. A documentary analysis was used to examine statistics of bullying incidences in six countries based on official reports by UNICEF in Myanmar and the Philippines, Organization for Economic Cooperation and Development (OECD) reports in Singapore and Thailand, and the Report on Bullying Index in Malaysia. This comparative analysis is important to provide an overal picture of students wellbeing. Findings revealed that various categories of bullying often occur in schools, including physical bullying, psychological bullying, and cyberbullying. Results also show that bullying incidences are alarming in all countries and it requires strategic action plan to prevent it. Analysis also indicate that some school children experienced of bullying in all the six ASEAN countries. Although various prevention strategies have been proposed in the past, any preventive action strategies implemented are unique and may not always be effective in all situations in all cultures. Therefore, a comprehensive bullying prevention strategy that is compatible with the socio-cultural values needs to be formulated in each country; so that bullying incidences might be prevented. Creating a positive school environment to prevent bullying incidences, simultenously cretes a school as a safe and peaceful place are really needed.